Synergies between special interest tourism and production systems based on traditional and intercultural knowledge - Aravena Paillalef, Gustavo; Barchiesi Ferrari, Claudia (Universidad Academia de Humanismo Cristiano, 2020)
In the context of peasant economies, which develop in geographic sectors where their ecosystems are fragile from the productive point of view, due to soil limitations, topography, climatic conditions such as cold, rain and snow, it is not easy to identify alternatives for sustainable economic development that allows to overcome subsistence situations. However, in the case of peasant family agriculture settled in the territories of the agroecological zone of the Andean Cordillera, it has a potential for future development associated with tourism initiatives of special interests with production systems based on traditional knowledge and management and intercultural. In this context, the need arises to analyze their potential synergies with initiatives associated with special interest tourism and with the proposal of a Heritage Route associated with mountain production systems.